Lumpy Investment and State-Dependent Pricing in General Equilibrium - Michael Reiter; Tommy Sveen; Lutz Weinke (Norges Bank, 2009)
The lumpy nature of plant-level investment is generally not taken into account in the context of monetary theory (see, e.g., Christiano et al. 2005 and Woodford 2005). We formulate a generalized (S,s) pricing and investment model which is empirically more plausible along that dimension. Surprisingly, our main result shows that the presence of lumpy investment casts doubt on the ability of sticky prices to imply a quantitatively relevant monetary transmission mechanism.
hdl:11250/2497639
Keywords: E22; E31; E32; 330; lumpy investment; sticky prices